1990
DOI: 10.1897/1552-8618(1990)9[1171:toiaos]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Inorganic and Organic Selenium to Daphnia Magna (Cladocera) and Chironomus Riparius (Diptera)

Abstract: Elevated concentrations of selenium (Se) have been previously measured in biota sampled from the Kesterson National Wildlife Refuge (KNWR) in the San Joaquin Valley of central California. We conducted acute and chronic toxicity tests with the cladoceran Daphnia magna and the midge Chironomus riparius to determine the toxicity or bioaccumulation of waterborne Se in a reconstituted water sinilar to the San Joaquin River. Daphnids were more acutely sensitive than midges to the toxic effects of inorganic Se. An or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
41
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 15 publications
8
41
1
Order By: Relevance
“…Our results support the work of earlier researchers [13,14,17,18,37,38] who found that Se had a negative impact on aquatic biota at concentrations Ͻ100 g/L, and as low as 10 g/L in some food chain studies. Most studies have found fish to be sensitive to Se only under conditions of long-term exposure from both food and water.…”
Section: Resultssupporting
confidence: 93%
“…Our results support the work of earlier researchers [13,14,17,18,37,38] who found that Se had a negative impact on aquatic biota at concentrations Ͻ100 g/L, and as low as 10 g/L in some food chain studies. Most studies have found fish to be sensitive to Se only under conditions of long-term exposure from both food and water.…”
Section: Resultssupporting
confidence: 93%
“…Selenium was not successfully measured in many of the QD exposure solutions due to high Se detection limits on the ICP-AES. However, selenium was not seen as important in the acute toxicity of QDs, because the total selenium concentrations in even our highest QD treatments were below toxicologically relevant concentrations for acute tests [24].…”
Section: Stabilitymentioning
confidence: 68%
“…and the epibenthic amphipod P. australis in water-only exposures. Ingersoll et al (1990) referred to the similar extreme acute sensitivity of Daphnia magna to selenomethionone, although the toxicity of selenomethionone was not studied in detail.…”
Section: Discussionmentioning
confidence: 99%
“…The toxicity risk posed by selenium is primarily from dietary uptake, which is a result of the propensity of selenium to cycle through the sediment and enter the benthic}detrital food web. This dietary uptake of selenium ultimately causes growth and reproductive impairment in "sh, crustaceans, and other wildlife (Ahsanullah and Brand, 1985;Hamilton et al, 1990;Ingersoll et al, 1990). The chronic toxicity of the seleno-amino acids to Corophium sp.…”
Section: Toxicity Of Selenomethionine To Amphipodsmentioning
confidence: 99%
See 1 more Smart Citation